From One Place to Another : The Transnational Mobility of Contemporary Francophone sub-Saharan African Writers - (:unkn) unknown (My University, 2011)
For authors producing contemporary African literature, there is a tension between centrifugal and centripetal forces within and outside the African continent. How can this geographical tension be measured empirically, in a hierarchical literary and publishing universe? Can one establish a link between the migratory trajectory of these authors and their social and literary success? This article undertakes a sociological analysis of 404 biographies of Francophone sub-Saharan African writers by considering a series of indicators related to national origin, geographic settlement, and displacement. These authors were active between 1983 and 2008 and socialized, at least as children, in Francophone sub-Saharan Africa; additional attention is also paid to a subgroup of 151 more well-known authors. The article confirms the importance of the transnational mobility of these writers, inseparable from those forms of cultural domination that drive globalization. The centrality of France is confirmed in this dynamic: residence there privileges publication and recognition. But the findings also point to other geographic points which play the role of literary centers: the USA, Belgium, Germany, and, to a lesser extent, Switzerland and Canada. Above all, a new vitality has emerged in the publishing industry in a number of African countries which are centers of writing and literary production, of which Ivory Coast and Senegal are pre-eminent examples.
Keywords: African Research